Pembangunan Ekonomi Islam - Maulana , Ahnaf; Rusmini, Rusmini; Mukaromah , Vitayatul; Nafisa, Yusro (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
Along with developments in this era of globalization, it is the hope of each individual to look at a bright future with diverse human life conditions by fulfilling various existing needs, Islam is present which offers a concept in growing and developing the communitys economy so as to create social welfare as a whole. This concept does not only apply to Muslims, but also to all individuals on this earth because it is in line with the definition of Islam as a religion that is rahmatan lil alamin, which means Grace to all nature. The emergence of Islamic economics is aimed at building an economic framework based on religious sources so that a state economic order is formed based on justice as well as equality for the birth of a civilized society under the protection of Allah SWT. Every human activity in Islam has a principle with a measurement of the value of his merits and sins. Everything that is done by humans and has the value of worship will get a reward, and everything that contains the value of harm or harms one party will be worth a sin in the eyes of the creator. In life and quality formation of human character, Islam bases economic development on the formation of each individual who is directed to God as controlling every human action in daily mu'amalah. people who prioritize economic changes only with spiritual matters, they still deviate from God's law, each economic actor and government play an important role in creating prosperity in every level of society.